Kualitas Pelayanan, Kualitas Produk, dan Harga Meningkatkan Kepuasan Pelanggan Richeese - Nurul Zubair; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2026)
This study aims to analyze the effect of service quality, product quality, and price perception on customer satisfaction at Richeese Factory Mampang branch. The research uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS), analyzed using SmartPLS 3 software. The research data were obtained from 150 respondents who are customers of Richeese Factory Mampang branch through the distribution of questionnaires using a Likert scale. The results show that service quality, product quality, and price perception have a positive and significant effect on customer satisfaction. Among these three variables, price perception has the most dominant influence on customer satisfaction, with a path coefficient value of 0.547 and an effect size of 0.450. The coefficient of determination (R²) value of 0.685 indicates that the research model is able to explain 68.5% of the variation in customer satisfaction. These findings suggest that, in addition to maintaining service quality and product quality, companies need to set prices in accordance with customers’ perceived value in order to improve customer satisfaction in the fast-food restaurant industry.